The Utilization of Artificial Intelligence to Equip Senior High School Students with Knowledge to Build Sustainable Businesses - Patricia; Calandra Alencia Haryani (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
In today’s digital era, artificial intelligence (AI) has become one of the most transformative innovations driving business advancement across various sectors. This workshop introduces high school students to artificial intelligence (AI) as a powerful tool for building and growing sustainable businesses. Through interactive presentations and hands-on activities, students will learn basic AI concepts, explore its applications in business, and understand how AI can enhance efficiency, drive innovation, and increase competitiveness. Real-life case studies and AI simulations will help students identify practical opportunities and challenges in business. Students will also create and present their own AI-based business ideas, enabling them to apply what they’ve learned to real-world contexts. This experience builds foundational skills in AI and entrepreneurship, encouraging creative and strategic thinking. Aligned with Sustainable Development Goal (SDG) 8, which promotes inclusive economic growth, productive employment, and decent work, the workshop empowers students to become future innovators and encourages sustainable business practices that contribute to economic development that create positive social impact in their communities.